Design and 3D printing of scaffolds and tissues - An, Jia (2018)
A growing number of three-dimensional (3D)-printing processes have been applied to tissue engineering. This paper presents a state-of-the-art study of 3D-printing technologies for tissue-engineering applications, with particular focus on the development of a computer-aided scaffold design system; the direct 3D printing of functionally graded scaffolds; the modeling of selective laser sintering (SLS) and fused deposition modeling (FDM) processes; the indirect additive manufacturing of scaffolds, with both micro and macro features; the development of a bioreactor; and 3D/4D bioprinting. Technological limitations will be discussed so as to highlight the possibility of future improvements for new 3D-printing methodologies for tissue engineering.